2015
DOI: 10.1016/j.jds.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and proteomic analyses of the biofilms generated by Streptococcus mutans isolated from caries-active and caries-free adults

Abstract: Background/purpose: Biofilm formation by Streptococcus mutans is a prerequisite for the development of caries. Different strains of S. mutans may differ in their capacity in biofilm formation and protein expression. The objective of this study was to investigate the morphological features and proteomes of biofilms of S. mutans clinical isolates. Materials and methods: Clinical strains isolated from caries-active (SM 593) and caries-free (SM 18) adults were cultured on polystyrene sheets in tryptoneepolypeptone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…This same expression pattern between MIG1 and the FLO1, 5 , and 9 genes was observed in biofilm formation, suggesting these FLO genes were regulated by MIG1 . Mature biofilms were divided into three parts: the outer, intermediate, and inner surface layers ( Jiang et al, 2015 ). Although cells-surface adhesion is a primary step in biofilm formation and critical for forming the inner biofilm layer ( Periasamy et al, 2012 ), cell–cell adhesions appeared more requisite in the intermediate and outer layers.…”
Section: Resultsmentioning
confidence: 99%
“…This same expression pattern between MIG1 and the FLO1, 5 , and 9 genes was observed in biofilm formation, suggesting these FLO genes were regulated by MIG1 . Mature biofilms were divided into three parts: the outer, intermediate, and inner surface layers ( Jiang et al, 2015 ). Although cells-surface adhesion is a primary step in biofilm formation and critical for forming the inner biofilm layer ( Periasamy et al, 2012 ), cell–cell adhesions appeared more requisite in the intermediate and outer layers.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm was proposed to play a crucial role in acid tolerant of S. mutans [ 34 ]. In our previous study, we also found that SM593 exhibited a superior capacity to form more complex biofilm than SM18 and ATCC 25175 [ 35 ]. Therefore, we speculate that more complex structure of biofilm and greater ability of SM593 to form biofilm could partly explain a stronger capability of SM593 biofilm to tolerate low pH and grow compared with SM18 biofilm and ATCC 25175.…”
Section: Discussionmentioning
confidence: 99%
“…mutans strains with dental caries. In fact, the authors discovered significant differences in their abilities to form biofilms and in their profiles of protein expression [ 57 ].…”
Section: Etiology and Pathogenesis Of Dental Cariesmentioning
confidence: 99%